A communication protocol for open environment housings - Baptista, Vasco
The growing popularity of wireless communications together with trend of cost reduction is fueling the development of services and technologies aiming at improving the welfare and comfort of people at home. The B-live Wireless system was developed in the scope of an ongoing industry-backed research project that envisages the development of technologies and services to support healthy, productive and active citizens. This paper reports the wireless protocol enabling the support of real-time biosignal monitoring, localization services and event communication in open environment housings.